Burden of Itch in Patients with Basal Cell Carcinoma - Iwona Chlebicka; Aleksandra A. Stefaniak; Łukasz Matusiak; Jacek C. Szepietowski (Medical Journals Sweden, 2021)
The incidence of basal cell carcinoma has increased in recent years. The aim of this study was to analyse the influence of itch on quality of life and psychosocial status of patients with basal cell carcinoma. A total of 180 patients with basal cell carcinoma were included in the study. Itch intensity was assessed with Numerical Rating Scale and 4-Item Itch Questionnaire (4IIQ). Quality of life in basal cell carcinoma was assessed with the 36-item Short-Form Health Survey (SF-36), Dermatology Life Quality Index (DLQI), 6 Item Stigmatization Scale (6-ISS) and Beck Depression Inventory (BDI). Mean DLQI in the study group was 2.0 ± 2.0, while mean SF-36 was 71.38 ± 15.77 points. The intensity of itch assessed with 4IIQ correlated negatively with SF-36 (R = -0.48, p = 0.003). The mean ± SD BDI score was 6.16 ± 5.72 points and mean 6-ISS score was 0.66 ± 1.24. In conclusion, presence and intensity of itch may debilitate quality of life among patients with basal cell carcinoma.